Black phosphorene-graphene composite film, and preparation method and application thereof

CN122950409APending Publication Date: 2026-10-20BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510466378.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-14
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,现有黑磷材料的劣势在于体积膨胀大,电位高,电子电导较差,仍有较大的改进空间

Benefits of technology

[0035]本发明提供的磷碳复合膜兼具黑磷烯和石墨烯的优势,其中的黑磷烯组分发挥其独特的嵌锂导锂能力,石墨烯组分提供良好的导电性和柔韧性,两者所起作用协同配合,有效地抑制了锂金属电池在循环过程中的锂枝晶生长,最终显著提升了锂金属电池的综合性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005359325680000011
    Figure HDA0005359325680000011
  • Figure HDA0005359325680000012
    Figure HDA0005359325680000012
Patent Text Reader

Abstract

This invention belongs to the field of battery materials technology, and relates to a black phosphorus-graphene composite film, its preparation method, and its application. The black phosphorus-graphene composite film includes a phosphorus-carbon mixed layer and graphene layers disposed on both sides of the phosphorus-carbon mixed layer, wherein the phosphorus-carbon mixed layer is a mixture of black phosphorus and graphene; or, the black phosphorus-graphene composite film includes a black phosphorus layer and graphene layers disposed on both sides of the black phosphorus layer. The composite film provided by this invention combines the lithium-affinity properties of black phosphorus and the electrochemical activity of graphene, effectively suppressing lithium dendrite growth during lithium metal battery cycling and significantly improving the overall performance of lithium metal batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery materials technology, and relates to a phosphorus-carbon composite film, and more particularly to a black phosphorus-graphene composite film and its preparation method and application. Background Technology

[0002] Currently, high-energy-density novel lithium-ion batteries have become a research hotspot in the battery field. It is well known that improvements in battery performance largely depend on the performance of electrode materials. In recent years, widely applied electrochemical systems, such as lithium cobalt oxide-graphite, ternary-graphite, and lithium iron phosphate-graphite, have been limited by the traditional lithium insertion / extraction mode of anode materials, restricting further improvements in battery energy density. Therefore, the development of lithium metal batteries is of great significance. Lithium metal batteries offer higher energy density and superior lightweight design, but in practical applications, they still face many challenges, such as the adverse effects of lithium dendrite formation on battery safety and cycle life. How to more safely and effectively suppress lithium dendrite growth has become an urgent problem that those skilled in the art need to solve.

[0003] To overcome these problems, current research focuses on developing safer strategies to effectively suppress lithium dendrite growth and designing more stable battery structures. In lithium metal batteries, applying a lithiophilic layer to the negative electrode side is an effective means of suppressing lithium dendrite growth. Mainstream lithiophilic coatings include carbon materials, lithiophilic alloys or oxides, and lithiophilic polymers.

[0004] Among them, lithiophilic carbon materials are generally carbon-based substances such as graphite and carbon nanotubes, which have good electrical conductivity and chemical stability, but insufficient lithiophilicity; lithiophilic alloy materials are generally materials that can form stable compounds or alloys with lithium, with a strong ion diffusion coefficient, but high film brittleness; lithiophilic polymers are generally high molecular materials, with strong flexibility, but insufficient electrical conductivity and limited stability.

[0005] Furthermore, researchers have discovered that black phosphorus (a phosphorus allotrope with a layered structure) can serve as a negative electrode material for lithium-ion and sodium-ion batteries to extend their driving range. Black phosphorus undergoes intercalation and alloying reactions during lithium intercalation, offering advantages such as favorable lithium intercalation kinetics, suitability for fast charging, and high specific capacity, making it a promising candidate for the lithium-affinity layer in lithium-metal batteries. However, existing black phosphorus materials suffer from significant volume expansion, high potential, and poor electronic conductivity, indicating considerable room for improvement.

[0006] Therefore, obtaining a functional film with good flexibility, strong stability, and excellent electrical and lithium conductivity through multi-component composite design of lithium-loving materials is an effective means to improve the overall performance of lithium metal batteries. Summary of the Invention

[0007] The purpose of this invention is to provide a black phosphorus-graphene composite membrane, its preparation method and application. The composite membrane combines the lithiophilic properties of black phosphorus with the electrochemical activity of graphene, effectively suppressing the growth of lithium dendrites in lithium metal batteries during cycling and significantly improving the overall performance of lithium metal batteries.

[0008] To achieve this objective, the present invention adopts the following technical solution:

[0009] In a first aspect, the present invention provides a black phosphorus-graphene composite film, the black phosphorus-graphene composite film comprising a phosphorus-carbon mixed layer and graphene layers disposed on both sides of the phosphorus-carbon mixed layer, wherein the phosphorus-carbon mixed layer is a mixed layer of black phosphorus and graphene.

[0010] Alternatively, the black phosphorus-graphene composite film may include a black phosphorus layer and graphene layers disposed on both sides of the black phosphorus layer.

[0011] The phosphorus-carbon composite membrane provided by this invention combines the advantages of black phosphorus and graphene. The black phosphorus component exerts its unique lithium intercalation and conduction ability, while the graphene component provides good conductivity and flexibility. The two work together to effectively suppress the growth of lithium dendrites in lithium metal batteries during cycling, ultimately significantly improving the overall performance of lithium metal batteries.

[0012] Preferably, in the black phosphorus-graphene composite film, the mass percentage of black phosphorus is 10%-70%.

[0013] Preferably, in the phosphorus-carbon mixed layer, the mass ratio of black phosphorusene to graphene is (0.3-5):1.

[0014] Preferably, the total thickness of the black phosphorus-graphene composite film is 6-12 μm.

[0015] Preferably, the thickness ratio of the phosphorus-carbon mixed layer to the graphene layer is (3-6):1.

[0016] Preferably, the thickness ratio of the black phosphorus layer to the graphene layer is (3-5):1.

[0017] In a second aspect, the present invention provides a method for preparing a black phosphorus-graphene composite film as described in the first aspect, the method comprising the following steps:

[0018] (1) The black phosphorus particles were subjected to a first solvent stripping process to obtain a black phosphorus dispersion;

[0019] (2) The flake graphite was exfoliated with a second solvent to obtain a graphene dispersion;

[0020] (3) Black phosphorus dispersion and graphene dispersion were used to filter and form a membrane to obtain a black phosphorus-graphene composite membrane.

[0021] Steps (1) and (2) are not in any particular order.

[0022] This invention utilizes the sheet-like structure of black phosphorus and graphene, stacking them layer by layer during the filtration process to obtain a black phosphorus-graphene composite membrane, which can achieve large-area and efficient preparation and is conducive to large-scale promotion and application.

[0023] Preferably, the average particle size of the black scale particles and the flake graphite is 8-12 μm.

[0024] Preferably, the solvents used for the first solvent stripping and the second solvent stripping include any one or a combination of at least two of N-methylpyrrolidone, ethanol, ethylene glycol, isopropanol, or N,N-dimethylformamide.

[0025] Preferably, the ultrasonic power of the first solvent stripping and the second solvent stripping is 40-60 kHz, respectively.

[0026] Preferably, the ultrasonic time for the first solvent stripping and the second solvent stripping is 6-12 hours, respectively.

[0027] Preferably, the concentrations of the black phosphorus dispersion and the graphene dispersion are 0.5-1.5 mg / mL, respectively.

[0028] Preferably, after the filtration membrane is formed, it is washed and dried in sequence.

[0029] Preferably, the washing liquid used for washing includes any one or a combination of at least two of ethanol, acetone, isopropanol or deionized water.

[0030] Preferably, the drying temperature is 30-70°C.

[0031] Thirdly, the present invention provides a lithium metal anode sheet, comprising a phosphorus-carbon composite film and a lithium metal sheet stacked together, wherein the phosphorus-carbon composite film is the black phosphorus-graphene composite film as described in the first aspect.

[0032] Fourthly, the present invention provides a lithium metal battery comprising a lithium metal negative electrode as described in the third aspect.

[0033] Fifthly, the present invention provides a vehicle comprising a lithium metal battery as described in the fourth aspect.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] The phosphorus-carbon composite membrane provided by this invention combines the advantages of black phosphorus and graphene. The black phosphorus component exerts its unique lithium intercalation and conduction ability, while the graphene component provides good conductivity and flexibility. The two work together to effectively suppress the growth of lithium dendrites in lithium metal batteries during cycling, ultimately significantly improving the overall performance of lithium metal batteries. Attached Figure Description

[0036] Figure 1 These are schematic diagrams of the black phosphorus-graphene composite membrane structures provided in Examples 1-3 and Examples 5-7;

[0037] Figure 2 This is a schematic diagram of the black phosphorus-graphene composite membrane structure provided in Example 4;

[0038] Wherein: 1-phosphorus-carbon mixed layer; 2-graphene layer; 3-black phosphorus layer. Detailed Implementation

[0039] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0040] One embodiment of the present invention provides a black phosphorus-graphene composite film, the black phosphorus-graphene composite film comprising a phosphorus-carbon mixed layer and graphene layers disposed on both sides of the phosphorus-carbon mixed layer, wherein the phosphorus-carbon mixed layer is a mixed layer of black phosphorus and graphene.

[0041] Alternatively, the black phosphorus-graphene composite film may include a black phosphorus layer and graphene layers disposed on both sides of the black phosphorus layer.

[0042] The phosphorus-carbon composite membrane provided by this invention combines the advantages of black phosphorus and graphene. The black phosphorus component exerts its unique lithium intercalation and conduction ability, while the graphene component provides good conductivity and flexibility. The two work together to effectively suppress the growth of lithium dendrites in lithium metal batteries during cycling, ultimately significantly improving the overall performance of lithium metal batteries.

[0043] In some embodiments, the mass percentage of black phosphorus in the black phosphorus-graphene composite film is 10%-70%, for example, it can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or 70%, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0044] In some embodiments, the mass ratio of black phosphorus and graphene in the phosphorus-carbon mixed layer is (0.3-5):1, for example, it can be 0.3:1, 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1 or 5:1, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0045] In some embodiments, the total thickness of the black phosphorus-graphene composite film is 6-12 μm, for example, it can be 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm or 12 μm, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0046] In some embodiments, the thickness ratio of the phosphorus-carbon mixed layer to the graphene layer is (3-6):1, for example, it can be 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1 or 6:1, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0047] In some embodiments, the thickness ratio of the black phosphorus layer to the graphene layer is (3-5):1, for example, it can be 3:1, 3.2:1, 3.4:1, 3.6:1, 3.8:1, 4:1, 4.2:1, 4.4:1, 4.6:1, 4.8:1 or 5:1, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0048] One embodiment of the present invention provides a method for preparing the black phosphorus-graphene composite film described in any of the above embodiments, the preparation method comprising the following steps:

[0049] (1) The black phosphorus particles were subjected to a first solvent stripping process to obtain a black phosphorus dispersion;

[0050] (2) The flake graphite was exfoliated with a second solvent to obtain a graphene dispersion;

[0051] (3) Black phosphorus dispersion and graphene dispersion were used to filter and form a membrane to obtain a black phosphorus-graphene composite membrane.

[0052] Steps (1) and (2) are not in any particular order.

[0053] This invention utilizes the sheet-like structure of black phosphorus and graphene, stacking them layer by layer during the filtration process to obtain a black phosphorus-graphene composite membrane, which can achieve large-area and efficient preparation and is conducive to large-scale promotion and application.

[0054] In this invention, the order in which the black phosphorus dispersion and the graphene dispersion are filtered to form a film determines the membrane structure of the composite membrane. For example, if the graphene dispersion is poured in first for filtration and film formation, then a mixed solution of the black phosphorus dispersion and the graphene dispersion is poured on top for filtration and film formation, and finally the graphene dispersion is poured in for filtration and film formation, the resulting black phosphorus-graphene composite membrane includes a phosphorus-carbon mixed layer and graphene layers disposed on both sides of the phosphorus-carbon mixed layer, and the phosphorus-carbon mixed layer is a mixed layer of black phosphorus and graphene; similarly, if the graphene dispersion is poured in first for filtration and film formation, then the black phosphorus dispersion is poured on top for filtration and film formation, and finally the graphene dispersion is poured in for filtration and film formation, the resulting black phosphorus-graphene composite membrane includes a black phosphorus layer and graphene layers disposed on both sides of the black phosphorus layer.

[0055] In some embodiments, the average particle size of the black scale particles and the flake graphite is 8-12 μm, for example, it can be 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm or 12 μm, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0056] In some embodiments, the solvents used for the first solvent stripping and the second solvent stripping include any one or a combination of at least two of N-methylpyrrolidone, ethanol, ethylene glycol, isopropanol, or N,N-dimethylformamide. Typical but non-limiting combinations include combinations of N-methylpyrrolidone and ethanol, ethanol and ethylene glycol, ethylene glycol and isopropanol, isopropanol and N,N-dimethylformamide, N-methylpyrrolidone, ethanol and ethylene glycol, ethanol, ethylene glycol and isopropanol, or ethylene glycol, isopropanol and N,N-dimethylformamide.

[0057] In some embodiments, the ultrasonic power of the first solvent stripping and the second solvent stripping is 40-60 kHz, for example, it can be 40 kHz, 42 kHz, 44 kHz, 46 kHz, 48 kHz, 50 kHz, 52 kHz, 54 kHz, 56 kHz, 58 kHz or 60 kHz, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0058] In some embodiments, the ultrasonic time for the first solvent stripping and the second solvent stripping is 6-12 hours, for example, it can be 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 9.5 hours, 10 hours, 10.5 hours, 11 hours, 11.5 hours or 12 hours, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0059] In some embodiments, the concentrations of the black phosphorus dispersion and the graphene dispersion are 0.5-1.5 mg / mL, for example, 0.5 mg / mL, 0.6 mg / mL, 0.7 mg / mL, 0.8 mg / mL, 0.9 mg / mL, 1 mg / mL, 1.1 mg / mL, 1.2 mg / mL, 1.3 mg / mL, 1.4 mg / mL or 1.5 mg / mL, but are not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0060] In some embodiments, the membrane is washed and dried sequentially after filtration.

[0061] In some embodiments, the washing liquid used for washing includes any one or a combination of at least two of ethanol, acetone, isopropanol, or deionized water. Typical but non-limiting combinations include combinations of ethanol and acetone, acetone and isopropanol, isopropanol and deionized water, ethanol, acetone and isopropanol, or acetone, isopropanol and deionized water.

[0062] In some embodiments, the drying temperature is 30-70°C, for example, it can be 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C or 70°C, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0063] One embodiment of the present invention provides a lithium metal anode sheet, comprising a phosphorus-carbon composite film and a lithium metal sheet stacked together, wherein the phosphorus-carbon composite film is the black phosphorus-graphene composite film described in any of the above embodiments.

[0064] One embodiment of the present invention provides a lithium metal battery, the lithium metal battery containing the lithium metal negative electrode sheet described in any of the above embodiments.

[0065] One embodiment of the present invention provides a vehicle comprising a lithium metal battery as described in any of the above embodiments.

[0066] The numerical range described in this invention includes not only the point values ​​listed above, but also any point values ​​within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values ​​included in the range.

[0067] Example 1

[0068] This embodiment provides a black phosphorus-graphene composite film, such as... Figure 1 As shown, the black phosphorus-graphene composite film includes a phosphorus-carbon mixed layer 1 and graphene layers 2 disposed on both sides of the phosphorus-carbon mixed layer 1, and the phosphorus-carbon mixed layer 1 is a mixed layer of black phosphorus and graphene.

[0069] Specifically, in the black phosphorus-graphene composite film, the mass percentage of black phosphorus is 50%; in the phosphorus-carbon mixed layer 1, the mass ratio of black phosphorus to graphene is 3:1; the total thickness of the black phosphorus-graphene composite film is 6 μm, and the thickness ratio of the phosphorus-carbon mixed layer 1 to the graphene layer 2 is 4:1.

[0070] This embodiment also provides a method for preparing the above-mentioned black phosphorus-graphene composite film, which specifically includes the following steps:

[0071] (1) Using black phosphorus particles (average particle size of 10 μm) as raw material and N-methylpyrrolidone as solvent, a black phosphorus dispersion with a concentration of 1 mg / mL was obtained by sonication at a power of 50 kHz for 9 h.

[0072] (2) Using flake graphite (average particle size of 10 μm) as raw material and N-methylpyrrolidone as solvent, the graphene dispersion with a concentration of 1 mg / mL was obtained by sonication at a power of 50 kHz for 9 h.

[0073] (3) First, pour graphene dispersion into the filtration device for filtration to form a film. Then, pour a mixed solution of black phosphorus dispersion and graphene dispersion onto it for filtration to form a film. Finally, pour graphene dispersion into it for filtration to form a film. After washing with acetone and deionized water in sequence, dry it in an argon atmosphere at 50°C to obtain a black phosphorus-graphene composite film.

[0074] Example 2

[0075] This embodiment provides a black phosphorus-graphene composite film, such as... Figure 1 As shown, the black phosphorus-graphene composite film includes a phosphorus-carbon mixed layer 1 and graphene layers 2 disposed on both sides of the phosphorus-carbon mixed layer 1, and the phosphorus-carbon mixed layer 1 is a mixed layer of black phosphorus and graphene.

[0076] Specifically, in the black phosphorus-graphene composite film, the mass percentage of black phosphorus is 33.3%; in the phosphorus-carbon mixed layer 1, the mass ratio of black phosphorus to graphene is 1:1; the total thickness of the black phosphorus-graphene composite film is 6 μm, and the thickness ratio of the phosphorus-carbon mixed layer 1 to the graphene layer 2 is 4:1.

[0077] This embodiment also provides a method for preparing the above-mentioned black phosphorus-graphene composite film, which specifically includes the following steps:

[0078] (1) Using black phosphorus particles (average particle size of 10 μm) as raw material and N-methylpyrrolidone as solvent, a black phosphorus dispersion with a concentration of 1 mg / mL was obtained by sonication at a power of 50 kHz for 9 h.

[0079] (2) Using flake graphite (average particle size of 10 μm) as raw material and N-methylpyrrolidone as solvent, the graphene dispersion with a concentration of 1 mg / mL was obtained by sonication at a power of 50 kHz for 9 h.

[0080] (3) First, pour graphene dispersion into the filtration device for filtration to form a film. Then, pour a mixed solution of black phosphorus dispersion and graphene dispersion onto it for filtration to form a film. Finally, pour graphene dispersion into it for filtration to form a film. After washing with acetone and deionized water in sequence, dry it in an argon atmosphere at 50°C to obtain a black phosphorus-graphene composite film.

[0081] Example 3

[0082] This embodiment provides a black phosphorus-graphene composite film, such as... Figure 1 As shown, the black phosphorus-graphene composite film includes a phosphorus-carbon mixed layer 1 and graphene layers 2 disposed on both sides of the phosphorus-carbon mixed layer 1, and the phosphorus-carbon mixed layer 1 is a mixed layer of black phosphorus and graphene.

[0083] Specifically, in the black phosphorus-graphene composite film, the mass percentage of black phosphorus is 16.6%; in the phosphorus-carbon mixed layer 1, the mass ratio of black phosphorus to graphene is 0.3:1; the total thickness of the black phosphorus-graphene composite film is 6 μm, and the thickness ratio of the phosphorus-carbon mixed layer 1 to the graphene layer 2 is 4:1.

[0084] This embodiment also provides a method for preparing the above-mentioned black phosphorus-graphene composite film, which specifically includes the following steps:

[0085] (1) Using black phosphorus particles (average particle size of 10 μm) as raw material and N-methylpyrrolidone as solvent, a black phosphorus dispersion with a concentration of 1 mg / mL was obtained by sonication at a power of 50 kHz for 9 h.

[0086] (2) Using flake graphite (average particle size of 10 μm) as raw material and N-methylpyrrolidone as solvent, the graphene dispersion with a concentration of 1 mg / mL was obtained by sonication at a power of 50 kHz for 9 h.

[0087] (3) First, pour graphene dispersion into the filtration device for filtration to form a film. Then, pour a mixed solution of black phosphorus dispersion and graphene dispersion onto it for filtration to form a film. Finally, pour graphene dispersion into it for filtration to form a film. After washing with acetone and deionized water in sequence, dry it in an argon atmosphere at 50°C to obtain a black phosphorus-graphene composite film.

[0088] Example 4

[0089] This embodiment provides a black phosphorus-graphene composite film, such as... Figure 2 As shown, the black phosphorus-graphene composite film includes a black phosphorus layer 3 and graphene layers 2 disposed on both sides of the black phosphorus layer 3.

[0090] Specifically, in the black phosphorus-graphene composite film, the mass percentage of black phosphorus is 66.6%; the total thickness of the black phosphorus-graphene composite film is 6 μm, and the thickness ratio of the phosphorus-carbon mixed layer 1 to the graphene layer 2 is 4:1.

[0091] This embodiment also provides a method for preparing the above-mentioned black phosphorus-graphene composite film, which specifically includes the following steps:

[0092] (1) Using black phosphorus particles (average particle size of 10 μm) as raw material and N-methylpyrrolidone as solvent, a black phosphorus dispersion with a concentration of 1 mg / mL was obtained by sonication at a power of 50 kHz for 9 h.

[0093] (2) Using flake graphite (average particle size of 10 μm) as raw material and N-methylpyrrolidone as solvent, the graphene dispersion with a concentration of 1 mg / mL was obtained by sonication at a power of 50 kHz for 9 h.

[0094] (3) First, pour graphene dispersion into the filtration device for filtration to form a film. Then, pour black phosphorus dispersion onto it for filtration to form a film. Finally, pour graphene dispersion into it for filtration to form a film. After washing with acetone and deionized water in sequence, dry in an argon atmosphere at 50°C to obtain a black phosphorus-graphene composite film.

[0095] Example 5

[0096] This embodiment provides a black phosphorus-graphene composite film, such as... Figure 1 As shown, the black phosphorus-graphene composite film includes a phosphorus-carbon mixed layer 1 and graphene layers 2 disposed on both sides of the phosphorus-carbon mixed layer 1, and the phosphorus-carbon mixed layer 1 is a mixed layer of black phosphorus and graphene.

[0097] Specifically, in the black phosphorus-graphene composite film, the mass percentage of black phosphorus is 50%; in the phosphorus-carbon mixed layer 1, the mass ratio of black phosphorus to graphene is 2:1; the total thickness of the black phosphorus-graphene composite film is 8 μm, and the thickness ratio of the phosphorus-carbon mixed layer 1 to the graphene layer 2 is 6:1.

[0098] This embodiment also provides a method for preparing the above-mentioned black phosphorus-graphene composite film, which specifically includes the following steps:

[0099] (1) Using black phosphorus particles (average particle size of 10 μm) as raw material and N-methylpyrrolidone as solvent, a black phosphorus dispersion with a concentration of 1 mg / mL was obtained by sonication at a power of 50 kHz for 9 h.

[0100] (2) Using flake graphite (average particle size of 10 μm) as raw material and N-methylpyrrolidone as solvent, the graphene dispersion with a concentration of 1 mg / mL was obtained by sonication at a power of 50 kHz for 9 h.

[0101] (3) First, pour graphene dispersion into the filtration device for filtration to form a film. Then, pour a mixed solution of black phosphorus dispersion and graphene dispersion onto it for filtration to form a film. Finally, pour graphene dispersion into it for filtration to form a film. After washing with acetone and deionized water in sequence, dry it in an argon atmosphere at 50°C to obtain a black phosphorus-graphene composite film.

[0102] Example 6

[0103] This embodiment provides a black phosphorus-graphene composite film, such as... Figure 1 As shown, the black phosphorus-graphene composite film includes a phosphorus-carbon mixed layer 1 and graphene layers 2 disposed on both sides of the phosphorus-carbon mixed layer 1, and the phosphorus-carbon mixed layer 1 is a mixed layer of black phosphorus and graphene.

[0104] Specifically, in the black phosphorus-graphene composite film, the mass percentage of black phosphorus is 50%; in the phosphorus-carbon mixed layer 1, the mass ratio of black phosphorus to graphene is 5:1; the total thickness of the black phosphorus-graphene composite film is 10 μm, and the thickness ratio of the phosphorus-carbon mixed layer 1 to the graphene layer 2 is 3:1.

[0105] This embodiment also provides a method for preparing the above-mentioned black phosphorus-graphene composite film, which specifically includes the following steps:

[0106] (1) Using black phosphorus particles (average particle size of 10 μm) as raw material and N-methylpyrrolidone as solvent, a black phosphorus dispersion with a concentration of 1 mg / mL was obtained by sonication at a power of 50 kHz for 9 h.

[0107] (2) Using flake graphite (average particle size of 10 μm) as raw material and N-methylpyrrolidone as solvent, the graphene dispersion with a concentration of 1 mg / mL was obtained by sonication at a power of 50 kHz for 9 h.

[0108] (3) First, pour graphene dispersion into the filtration device for filtration to form a film. Then, pour a mixed solution of black phosphorus dispersion and graphene dispersion onto it for filtration to form a film. Finally, pour graphene dispersion into it for filtration to form a film. After washing with acetone and deionized water in sequence, dry it in an argon atmosphere at 50°C to obtain a black phosphorus-graphene composite film.

[0109] Example 7

[0110] This embodiment provides a black phosphorus-graphene composite film, such as... Figure 1 As shown, the black phosphorus-graphene composite film includes a phosphorus-carbon mixed layer 1 and graphene layers 2 disposed on both sides of the phosphorus-carbon mixed layer 1, and the phosphorus-carbon mixed layer 1 is a mixed layer of black phosphorus and graphene.

[0111] Specifically, in the black phosphorus-graphene composite film, the mass percentage of black phosphorus is 50%; in the phosphorus-carbon mixed layer 1, the mass ratio of black phosphorus to graphene is 3:1; the total thickness of the black phosphorus-graphene composite film is 12 μm, and the thickness ratio of the phosphorus-carbon mixed layer 1 to the graphene layer 2 is 4:1.

[0112] This embodiment also provides a method for preparing the above-mentioned black phosphorus-graphene composite film, which specifically includes the following steps:

[0113] (1) Using black phosphorus particles (average particle size of 10 μm) as raw material and N-methylpyrrolidone as solvent, a black phosphorus dispersion with a concentration of 1 mg / mL was obtained by sonication at a power of 50 kHz for 9 h.

[0114] (2) Using flake graphite (average particle size of 10 μm) as raw material and N-methylpyrrolidone as solvent, the graphene dispersion with a concentration of 1 mg / mL was obtained by sonication at a power of 50 kHz for 9 h.

[0115] (3) First, pour graphene dispersion into the filtration device for filtration to form a film. Then, pour a mixed solution of black phosphorus dispersion and graphene dispersion onto it for filtration to form a film. Finally, pour graphene dispersion into it for filtration to form a film. After washing with acetone and deionized water in sequence, dry it in an argon atmosphere at 50°C to obtain a black phosphorus-graphene composite film.

[0116] Comparative Example 1

[0117] This comparative example provides a graphene monolayer film with a thickness of 6 μm, and the preparation method includes the following steps:

[0118] (1) Using flake graphite (average particle size of 10 μm) as raw material and N-methylpyrrolidone as solvent, a graphene dispersion with a concentration of 1 mg / mL was obtained by sonication at a power of 50 kHz for 9 h.

[0119] (2) Graphene dispersion was poured into the filtration device for filtration to form a film. After washing with acetone and deionized water, the film was dried in an argon atmosphere at 50°C to obtain a graphene monolayer film.

[0120] Comparative Example 2

[0121] This comparative example provides a black phosphorus monolayer film with a thickness of 6 μm, and the preparation method includes the following steps:

[0122] (1) Using black phosphorus particles (average particle size of 10 μm) as raw material and N-methylpyrrolidone as solvent, a black phosphorus dispersion with a concentration of 1 mg / mL was obtained by sonication at a power of 50 kHz for 9 h.

[0123] (2) Pour black phosphorus dispersion into the filtration device for filtration to form a membrane. After washing with acetone and deionized water in sequence, dry in an argon atmosphere at 50°C to obtain a black phosphorus monolayer membrane.

[0124] Performance testing

[0125] The performance of the membrane materials obtained in Examples 1-7 and Comparative Examples 1-2 was tested using button cells.

[0126] The coin cell assembly was carried out in an argon-atmospheric glove box. The positive electrode used ternary NCM622 as the active material, Super P+SWCNT as the conductive agent, and PVDF as the binder. The content of the positive electrode active material was 96wt%. The positive electrode sheet was made by mixing, coating and drying. The negative electrode used the above film material and a lithium metal sheet with a thickness of 100μm. The separator was a 7μm polyethylene separator. The electrolyte was 1M LiPF6 (EC / EMC / DMC=1 / 1 / 1,+1.0%VC+1.0%FEC).

[0127] The obtained button cells were placed in a 25°C constant temperature chamber for 3cls of 0.05C charge-discharge cycles with a voltage window of 2.8-4.4V. After small current cycling, 0.5C charge-discharge cycles were performed under the same voltage window. The 150cls cycle capacity retention rate of the cells was recorded. The relevant test results are shown in Table 1 below.

[0128] Table 1

[0129] Battery Composite membrane structure design Thickness design Black phosphorus ratio 150cls capacity retention Example 1 Graphene-phosphorus-carbon hybrid-graphene 1+4+1 50.0% 74.5% Example 2 Graphene-phosphorus-carbon hybrid-graphene 1+4+1 33.3% 72.5% Example 3 Graphene-phosphorus-carbon hybrid-graphene 1+4+1 16.6% 71.4% Example 4 Graphene-black phosphorus-graphene 1+4+1 66.6% 74.1% Example 5 Graphene-phosphorus-carbon hybrid-graphene 1+6+1 50% 78.4% Example 6 Graphene-phosphorus-carbon hybrid-graphene 2+6+2 50% 79.3% Example 7 Graphene-phosphorus-carbon hybrid-graphene 2+8+2 50% 80.2% Comparative Example 1 Graphene monolayer 6 0% 55.7% Comparative Example 2 Black phosphorus monolayer 6 100% 48.5% Blank example Membrane-free materials / / 32.3%

[0130] As shown in Table 1, compared with Comparative Examples 1-2 and the blank example, the cycle performance of the coin cell prepared by using the composite film provided in Examples 1-7 is significantly improved. This is because the use of the composite film effectively suppresses the growth of lithium dendrites in the lithium metal battery during the cycle.

[0131] Therefore, the phosphorus-carbon composite film provided by the present invention combines the advantages of black phosphorus and graphene. The black phosphorus component exerts its unique lithium intercalation and conduction ability, while the graphene component provides good conductivity and flexibility. The two work together to effectively suppress the growth of lithium dendrites in lithium metal batteries during cycling, and ultimately significantly improve the overall performance of lithium metal batteries.

[0132] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A black phosphorus-graphene composite film, characterized in that, The black phosphorus-graphene composite film includes a phosphorus-carbon mixed layer and graphene layers disposed on both sides of the phosphorus-carbon mixed layer, wherein the phosphorus-carbon mixed layer is a mixed layer of black phosphorus and graphene. Alternatively, the black phosphorus-graphene composite film may include a black phosphorus layer and graphene layers disposed on both sides of the black phosphorus layer.

2. The black phosphorus-graphene composite film according to claim 1, characterized in that, In the black phosphorus-graphene composite film, the mass percentage of black phosphorus is 10%-70%.

3. The black phosphorus-graphene composite film according to claim 1 or 2, characterized in that, In the phosphorus-carbon mixed layer, the mass ratio of black phosphorusene to graphene is (0.3-5):

1.

4. The black phosphorus-graphene composite film according to claim 1 or 2, characterized in that, The total thickness of the black phosphorus-graphene composite film is 6-12 μm.

5. The black phosphorus-graphene composite film according to claim 4, characterized in that, The thickness ratio of the phosphorus-carbon mixed layer to the graphene layer is (3-6):1; Alternatively, the thickness ratio of the black phosphorus layer to the graphene layer is (3-5):

1.

6. A method for preparing a black phosphorus-graphene composite film as described in any one of claims 1-5, characterized in that, The preparation method includes the following steps: (1) The black phosphorus particles were subjected to a first solvent stripping process to obtain a black phosphorus dispersion; (2) The flake graphite was exfoliated with a second solvent to obtain a graphene dispersion; (3) Black phosphorus dispersion and graphene dispersion were filtered to form a membrane, and a black phosphorus-graphene composite membrane was obtained. Steps (1) and (2) are not in any particular order.

7. The preparation method according to claim 6, characterized in that, The average particle size of the black scale particles and the flake graphite are 8-12 μm, respectively; And / or, the solvents used for the first solvent stripping and the second solvent stripping respectively include any one or a combination of at least two of N-methylpyrrolidone, ethanol, ethylene glycol, isopropanol or N,N-dimethylformamide; And / or, the ultrasonic power of the first solvent stripping and the second solvent stripping is 40-60 kHz, respectively; And / or, the ultrasonic time for the first solvent stripping and the second solvent stripping is 6-12 h, respectively; And / or, the concentrations of the black phosphorus dispersion and the graphene dispersion are 0.5-1.5 mg / mL, respectively; And / or, after the filtration membrane is formed, it is washed and dried in sequence; The washing liquid used in the washing process includes any one or a combination of at least two of ethanol, acetone, isopropanol, or deionized water, and the drying temperature is 30-70°C.

8. A lithium metal anode sheet, comprising a phosphorus-carbon composite film and a lithium metal sheet stacked together, characterized in that, The phosphorus-carbon composite membrane is the black phosphorus-graphene composite membrane as described in claim 1.

9. A lithium metal battery, characterized in that, The lithium metal battery contains the lithium metal negative electrode as described in claim 8.

10. A vehicle, characterized in that, The vehicle contains a lithium metal battery as described in claim 9.